Perancangan Ulang Interior Pusat Kebugaran Fit For Two Fitness Center Kota Bogor Dengan Pendekatan Well-being Design - Izza Khairullah, Muhammad; Adli Wismoyo, Erlana; Primiana Yuniati, Arnanti (eProceedings of Art & Design, 2024)
The shift in modern lifestyles has led to an increased demand for fitness facilities that accommodate a variety of exercise trends. The Fit for Two Fitness Center in Bukit Cimanggu City, Bogor, requires redesigning to meet these needs. This redesign aims to support the community's fitness activities by creating open, warm, and welcoming spaces that align with the residential culture. A "Well-Being Design" approach is employed to address identified design challenges, such as ventilation, space organization, and adherence to standards. The "Warmly Welcoming Fitness Spaces" concept is implemented through inclusive design and the use of interior elements that align with well-being principles. By focusing on current fitness trends and creating a warm atmosphere, this redesign is expected to enhance residents' quality of life, fostering an environment that supports their physical and mental well-being while preserving the community's culture. Keywords: interior, fitness center, well-being, sports.